Management of Student Support Systems in the 21st Century of the School Administrators of the Khun Yuam Mae Ngao Group, Khun Yum District, under the Mae Hong Son Primary Educational Service Area Office 1 - Wedchakit, Kanokorn; Sridadej, Surat; Prasomsuk, Teerapat; Sarawan, Prakob (MCU Haripunchai Review, 2025)
This research aims to 1) study Management of the Student Support System in the 21 st Century of the School Administrators of the Khun Yuam - Mae Ngao Group, Khun Yum District, under the Mae Hong Son Primary Educational Service Area Office 1 2) Study the development guidelines for the administration of the 21 st century student care system of the Khun Yuam-Mae Ngao School Group, Khun Yuam District, under the Office of the Primary Educational Service Area 1, Mae Hong Son. The population and sample consisted of school administrators, teachers, and educational personnel of the schools in the Khun Yuam-Mae Ngao School Group, Khun Yuam District, under the Office of the Primary Educational Service Area 1, Mae Hong Son, totaling 111 people. The instruments were a questionnaire with a reliability of 0.98 and in-depth interviews with 8 experts. The instruments were an interview form. Statistics and data analysis included percentages, means, standard deviations, and content analysis. The results of the research found that: 1) The administration of the 21 st century student care system of the Khun Yuam-Mae Ngao School Group, Khun Yuam District, Mae Hong Son Primary Educational Service Area Office 1 found that the aspects of student promotion and development, individual recognition of students, referrals, prevention and resolution of student problems, and student screening were all at a high level. 2) The guidelines for the development of the administration of the 21 st century student care system of the Khun Yuam-Mae Ngao School Group, Khun Yuam District, Mae Hong Son Primary Educational Service Area Office 1 found that Administrators should have a good and efficient administration process system, cooperation from all parties, and should increasingly use digital technology in the student care system in all aspects. They should operate appropriately, which should include principles for planning and procedures for systematically screening students, operating according to the plan, monitoring and inspecting operations according to the plan, and using the evaluation results to improve and develop for efficiency and effectiveness.